ANALISIS KUALITAS LAYANAN PADA PASIEN RAWAT JALAN DI RUMAH SAKIT NASIONAL DIPONEGORO KOTA SEMARANG - Qamaril Huda, Sabila; Zarkasyi Rahman, Amni; Hanani, Retna (Journal of Public Policy and Management Review, 2025)
This study was conducted to determine the quality of service to outpatients at Diponegoro National Hospital through a service quality approach. This research is a quantitative study using descriptive methods. Respondents in this study were 98 respondents, who were taken with non-probability sampling techniques and purposive sampling approaches. This research was conducted on outpatients with BPJS at Diponegoro National Hospital. Data collection techniques through observation, questionnaires and documentaries. The data was analysed using the SERVQUAL model. The results of the analysis show that the reliability indicator falls into quadrant IV, namely excessive, where patient perceptions of RSND services are higher than their expectations so that RSND has succeeded in exceeding patient expectations, especially in terms of timeliness and accuracy of service. Then the physical evidence indicator is in quadrant III, which is low priority, which indicates that although its performance is still less than optimal, this aspect does not have a major influence on overall patient satisfaction. Then, the responsiveness and assurance indicators are in quadrant II, namely maintaining achievement, where the performance provided by RSND in providing services to patients is good and needs to be maintained. Finally, the empathy indicator is in quadrant I, namely the main priority, which shows that this indicator has a weakness that is considered still not optimal which must be corrected immediately because it has a major influence on patient satisfaction. Based on these results, it is necessary to improve the empathy indicator with training for staff in order to provide optimal service for RSND patients.